2005
DOI: 10.1016/j.chemosphere.2005.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PCDD/Fs formation from dioxin precursors by calcium oxide

Abstract: Research aimed at understanding the inhibition effect of CaO on polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) formation form dioxins precursors, such as chlorophenols (CPs) and chlorobenzenes (CBs). The results indicated that a clear dioxin inhibition effect occurred both in open and sealed system when CaO was used. In the open system, PCDDs were the main congeners and the inhibition efficiency was all over 99% in the experiments. In the experiments with CaO, less than 0.1% of the initial PCP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The reaction time and temperature largely affect the suppressing ability of CaO. The suppression efficiency of PCDD/Fs by CaO surpassed 90% in a range of 280-450°C and a reaction time of 2 h using pentachlorophenol as a model precursor (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction time and temperature largely affect the suppressing ability of CaO. The suppression efficiency of PCDD/Fs by CaO surpassed 90% in a range of 280-450°C and a reaction time of 2 h using pentachlorophenol as a model precursor (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PCDD/Fs is of great concern because of their toxicity, which may induce hormonedependent cancers and reproductive effects in humans and wildlife (Liu et al, 2005;Wang et al, 2010). Thermal or combustion processes, chemical-industrial sources, and reservoirs are the three important categories of dioxin sources.…”
Section: Introductionmentioning
confidence: 99%
“…Toluene, n-hexane, and dichloromethane (all pesticide grade) were obtained from Fisher Scientific (Waltham, Massachusetts, USA). 13 C-labeled PCDD/Fs were obtained from Cambridge Isotope Laboratories (USA). PCCD/F impurities were removed from PCP (purity 99%) as follows.…”
Section: Methodsmentioning
confidence: 99%
“…However, the suppressing efficiencies of them is CaO ≈ BaO > MgO. Liu et al [13] also reported that CaO can efficiently inhibit the formation of PCDD/Fs from dioxin precursors. Nitrogen-containing compounds, including NH 3 , urea, and dimethylamine, also effectively inhibit PCDD/F formation [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation